Antimicrobial Activity of Syzygium polyanthum Wight (Walp.) Extract against Foodborne Pathogens in Food: A Potential Antimicrobial Agent for Natural Food Washing Solution - Suzita Ramli (Tanjung Malim, 2023)
Antimicrobial Activity of Syzygium polyanthum Wight (Walp.) Extract against Foodborne Pathogens in Food: A Potential Antimicrobial Agent for Natural Food Washing Solution by Suzita Ramli